High-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil and preparation method thereof
By introducing Co and appropriate amounts of Fe, Mg, and Nb into Cu-Ni-Si alloys and combining them with specific heat treatment processes, high-conductivity and high-heat-dissipation copper-cobalt-nickel-silicon alloy strips and foils were prepared. This solved the problem of insufficient conductivity and thermal conductivity of existing copper alloy materials in wireless charging technology, and realized alloy strips and foils with high conductivity and high thermal conductivity, meeting the high heat dissipation requirements of 5G mobile phones and new energy vehicles.
Patent Information
- Application Number
- CN202410725249.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-06
AI Technical Summary
Existing copper alloy materials cannot simultaneously meet the requirements of high conductivity, high thermal conductivity, and good resistance to high-temperature softening and stress relaxation in wireless charging technology, thus failing to meet the high conductivity and high heat dissipation requirements of fields such as 5G mobile phones and new energy vehicles.
High-conductivity and high-heat-dissipation copper-cobalt-nickel-silicon alloy strips and foils were used. By introducing Co element into Cu-Ni-Si alloy to form Co2Si precipitate, and combining appropriate amounts of Fe, Mg and Nb elements to refine the grains, a copper matrix grain size of 5~10μm and (Ni,Co)2Si precipitate size ≤15nm were prepared by using a two-stage solid solution and multi-stage deformation heat treatment process.
The conductivity and thermal conductivity of the alloy strip foil have been improved, with tensile strength ≥720MPa, conductivity ≥60%IACS, and thermal conductivity ≥255W/(m·K), meeting the high conductivity and high heat dissipation performance requirements of wireless fast charging fields such as 5G mobile phones and new energy vehicles.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper alloys, and in particular to a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil and a preparation method thereof. Background Art
[0002] As smartphones have more and more functions and larger screens, the battery life of mobile phones has become a major concern for consumers. Therefore, the application of wireless charging technology has become an important factor for consumer electronics companies represented by smartphones to expand market sales.
[0003] On the other hand, as an excellent wireless charging application scenario, car wireless charging does not require frequent plugging and unplugging of charging cables. It is a great tool to increase driving safety and improve the quality of life of car owners, and greatly improves the experience of using and charging mobile phones in the car.
[0004] Currently, wireless charging transmitters are on the rise in homes, offices (often embedded in furniture or electronic devices), cars, restaurants and public places, as well as public transportation. From the perspective of wireless charging technology itself, copper alloys are required to have not only high strength and conductivity, but also good resistance to high temperature softening and stress relaxation.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil to solve the above-mentioned technical problems.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil.
[0008] In order to achieve the above objectives, the following technical solutions are adopted:
[0009] In a first aspect, the present invention provides a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, which comprises, by mass percentage: Co 1.55%-1.66%, Ni 0.45%-0.55%, Si 0.43%-0.53%, Fe 0.01%-0.05%, Zn 0.015%-0.05%, Mg 0.01%-0.04%, Nb 0.05%-0.2%, and the balance is copper and unavoidable impurities;
[0010] In the high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, the grain size of the copper matrix is 5-10 μm, and the size of the (Ni, Co)2Si precipitated phase is ≤15 nm.
[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, comprising the following steps:
[0012] The materials are prepared according to the mass percentage, and then smelting, casting, hot rolling, first solution treatment, milling, first cold rolling, second solution treatment, second cold rolling, first aging treatment, third cold rolling and second aging treatment are carried out in sequence to prepare a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil.
[0013] As a further technical solution, the smelting temperature is 1250-1270°C;
[0014] The casting temperature is 1210-1230°C.
[0015] As a further technical solution, the hot rolling start temperature is 820~910℃;
[0016] The final rolling temperature of the hot rolling is 600-685°C;
[0017] The total processing rate of the hot rolling is 90% to 95%.
[0018] As a further technical solution, the temperature of the first solution treatment is 650-750°C, and the holding time is 0.5-2h.
[0019] As a further technical solution, the processing rate of the first cold rolling is 85% to 90%;
[0020] The processing rate of the second cold rolling is 70% to 80%;
[0021] The processing rate of the third cold rolling is 20% to 55%.
[0022] As a further technical solution, the second solid solution treatment is to continuously anneal the alloy material after the first cold rolling;
[0023] The temperature of the continuous annealing is 820-1040° C., and the speed is 15-25 m / min.
[0024] As a further technical solution, the temperature of the first aging treatment is 450-500°C, and the insulation time is 5-8h.
[0025] As a further technical solution, the second aging treatment is to anneal the alloy material after the third cold rolling in a bell-type annealing furnace, the annealing temperature is 350~450℃, and the holding time is 4~6h.
[0026] As a further technical solution, the first aging treatment and the second aging treatment are carried out under a protective atmosphere.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil provided by the present invention, on the basis of Cu-Ni-Si alloy, selects Co element to replace most of Ni element and Si element to form Co2Si precipitation phase precipitation, thereby reducing the solute solid solution degree of the alloy strip, and improving the electrical conductivity and thermal conductivity of the alloy strip foil while maintaining a high precipitation strengthening effect. At the same time, suitable Fe, Mg and Nb elements are conducive to grain refinement and promote the dispersion precipitation of precipitation phase; suitable Zn element can avoid the aggregation and growth of Co element precipitation phase to a certain extent. The copper matrix grain size of the strip foil is 5~10μm, the (Ni,Co)2Si precipitation phase size is ≤15nm, the tensile strength is ≥720MPa, the electrical conductivity is ≥60%IACS, and the thermal conductivity is ≥255W / (m·K), which can meet the needs of high conductivity and high heat dissipation performance in the wireless fast charging fields such as 5G mobile phones and new energy vehicles. DETAILED DESCRIPTION
[0029] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] In a first aspect, the present invention provides a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil material, mainly composed of Co, Ni, Si, Fe, Zn, Mg, Nb and Cu;
[0031] In the high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, the copper matrix grain size is 5~10μm, for example, it can be, but not limited to, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm; the (Ni,Co)2Si precipitation phase size is ≤15nm.
[0032] The Co element replaces Ni and forms a Co2Si precipitation phase with the silicon element, which reduces the solid solution degree of the alloy solute and improves the conductivity of the alloy. At the same time, the aging strengthening effect of the precipitation phase can also improve the strength of the alloy. In terms of mass percentage, the content of Co in the present invention can be, for example, but not limited to 1.55%, 1.58%, 1.60%, 1.63% or 1.66%.
[0033] The Ni element mainly forms a Ni2Si precipitation phase with the silicon element, which has a strong aging hardening effect, so that the alloy has good comprehensive properties. In terms of mass percentage, the Ni content in the present invention can be, for example, but not limited to 0.45%, 0.47%, 0.49%, 0.51%, 0.53% or 0.55%.
[0034] In the present invention, the content of Si may be, for example, but not limited to, 0.43%, 0.45%, 0.47%, 0.49%, 0.51% or 0.53%.
[0035] A small amount of Fe element addition can refine the grains, delay the recrystallization process, and reduce the tendency of ingot self-cracking. In terms of mass percentage, the Fe content in the present invention can be, for example, but not limited to, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%.
[0036] The Zn element can be dissolved in the alloy α phase to improve the mechanical properties of the alloy, reduce the alloy solidification temperature range, improve the fluidity of the alloy, and improve the casting performance. In terms of mass percentage, the Zn content in the present invention can be, for example, but not limited to, 0.015%, 0.02%, 0.03%, 0.04% or 0.05%.
[0037] The addition of Mg element promotes the precipitation of needle-shaped Ni5Si2, inhibits the growth of alloy grains, achieves the effect of refining grains and improving the mechanical properties of the alloy. In terms of mass percentage, the content of Mg in the present invention can be, for example, but not limited to, 0.01%, 0.02%, 0.03% or 0.04%.
[0038] The Nb element is almost not dissolved in the α phase under equilibrium conditions, and a trace amount of addition can also refine the grains and optimize the processing properties of the alloy. In terms of mass percentage, the content of Co in the present invention can be, for example, but not limited to, 0.05%, 0.1%, 0.15% or 0.2%.
[0039] Based on the Cu-Ni-Si alloy, the present invention uses Co element to replace most of the Ni element and Si element to form Co2Si precipitation phase, thereby reducing the solute solid solution degree of the alloy strip, and improving the electrical conductivity and thermal conductivity of the alloy strip foil while maintaining a high precipitation strengthening effect. However, during the alloy preparation process, the Co element precipitation phase is prone to coarsening after aging, which reduces the mechanical properties of the alloy. In order to solve the problem of precipitation phase coarsening, the present invention solves it from the perspective of alloy composition. In terms of alloy composition, Fe, Mg and Nb elements are added. A small amount of addition is beneficial to grain refinement and promotes the dispersion and precipitation of precipitation phases; a small amount of Zn element can narrow the solidification temperature range of the alloy, improve the fluidity of the alloy, improve the casting performance, obtain homogeneous high-quality ingots without surface defects, and avoid the aggregation and growth of Co element precipitation phases to a certain extent. The copper matrix grain size of the foil material provided by the present invention is 5-10 μm, the (Ni, Co) 2Si precipitated phase size is ≤15 nm, the tensile strength is ≥720 MPa, the electrical conductivity is ≥60% IACS, and the thermal conductivity is ≥255 W / (m·K).
[0040] In some optional embodiments, the foil has a thickness of 0.15-0.25 mm and a width of ≥600 mm.
[0041] In a second aspect, the present invention provides a method for preparing the above-mentioned high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, comprising the following steps:
[0042] The materials are prepared according to the mass percentage, and then smelting, casting, hot rolling, first solution treatment, milling, first cold rolling, second solution treatment, second cold rolling, first aging treatment, third cold rolling and second aging treatment are carried out in sequence to prepare a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil.
[0043] The preparation method provided by the present invention adopts a combined process of "secondary solid solution + multi-stage deformation heat treatment", wherein the secondary solid solution is characterized by high-temperature rapid solid solution treatment, the purpose of which is to fully dissolve the strip blank while avoiding grain growth; the multi-stage deformation heat treatment process achieves the purpose of refining the organizational grains and reducing the size of the precipitated phase by regulating the organizational structure. The preparation method is simple and efficient, and the prepared strip foil has good tensile strength, electrical conductivity and thermal conductivity, which can meet the requirements of high conductivity and high heat dissipation performance in the wireless fast charging field such as 5G mobile phones and new energy vehicles.
[0044] In some optional embodiments, the smelting temperature may be, for example, but not limited to, 1250° C., 1260° C. or 1270° C.;
[0045] The casting temperature may be, for example, but not limited to, 1210°C, 1220°C or 1230°C.
[0046] In some optional embodiments, during the smelting process, the alloy raw materials are added with electrolytic copper, 20% Cu-Ni intermediate alloy (Cu-Ni intermediate alloy with Ni mass accounting for 20%, the same below), 20% Cu-Si intermediate alloy, and Co metal in sequence according to the mass ratio of the components. After the above metal raw materials are melted, they are stirred and mixed once, and then iron wire, zinc ingot, 10% Cu-Mg intermediate alloy and Nb metal are added. After melting, they are stirred and mixed twice to make the metal melt evenly mixed.
[0047] In some optional embodiments, the diameter of the iron wire is 0.5~2mm.
[0048] In some optional embodiments, the casting includes: pouring the alloy melt obtained by smelting into a crystallizer cooled by circulating water, and pulling it out through a traction device after cooling by cooling water, so as to obtain an ingot; the traction device first casts at a speed of 55-65 mm / min, and then maintains a speed of 75-85 mm / min for casting; the cooling water is firstly cast at a speed of 50-60 m 3 / h flow rate for cooling, and then maintain 80~100m 3 / h flow rate for cooling.
[0049] In some optional embodiments, the size of the ingot obtained by casting is ≥630 mm in width and ≥190 mm in thickness.
[0050] In some optional embodiments, the hot rolling start temperature may be, for example, but not limited to, 820°C, 840°C, 860°C, 880°C, 900°C or 910°C;
[0051] The final rolling temperature of the hot rolling may be, for example, but not limited to, 600°C, 620°C, 640°C, 660°C or 685°C;
[0052] The total processing rate of the hot rolling may be, for example, but not limited to, 90%, 91%, 92%, 93%, 94% or 95%.
[0053] In some optional embodiments, the temperature of the first solution treatment may be, for example, but not limited to, 650° C., 700° C. or 750° C., and the holding time may be, for example, but not limited to, 0.5 h, 1 h, 1.5 h or 2 h.
[0054] Through the first solution treatment, the solute elements are dissolved into the matrix, while the hot-rolled strip is homogenized and rolling defects are eliminated.
[0055] During the hot rolling solution process, the surface of the ingot is severely oxidized. In some optional embodiments, a double-sided milling step is used, with a milling cutter speed of 650-850 rpm and a machine train running speed of 3-6 m / min for 1-3 times of milling.
[0056] In some optional implementations, the milling surface processing rate is 10% to 50%, the roller speed is 200 to 300 m / min, and the rolling force per pass is ≤ 630 tons.
[0057] In some optional embodiments, the processing rate of the first cold rolling may be, for example, but not limited to, 85%, 86%, 87%, 88%, 89% or 90%;
[0058] The processing rate of the second cold rolling may be, for example, but not limited to, 70%, 72%, 74%, 76%, 78% or 80%;
[0059] The processing rate of the third cold rolling may be, for example, but not limited to, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%.
[0060] In some optional embodiments, during the first cold rolling, the roll gap is controlled by controlling the rolling force to be ≤ 630 tons during billet opening to ensure the shape of the alloy plate after rolling.
[0061] In some optional embodiments, the second solution treatment is vertical continuous annealing of the alloy material after the first cold rolling;
[0062] The temperature of the continuous annealing may be, for example, but not limited to 820°C, 870°C, 920°C, 970°C or 1040°C, and the speed may be, for example, but not limited to 15m / min, 17m / min, 19m / min, 21m / min, 23m / min or 25m / min.
[0063] In some optional embodiments, the temperature of the first aging treatment may be, for example, but not limited to, 450°C, 460°C, 470°C, 480°C, 490°C or 500°C, and the holding time may be, for example, but not limited to, 5h, 6h, 7h or 8h.
[0064] In some optional embodiments, the second aging treatment is to anneal the alloy material after the third cold rolling in a bell-type annealing furnace, and the annealing temperature can be, for example, but not limited to 350°C, 370°C, 390°C, 410°C, 430°C or 450°C, and the holding time can be, for example, but not limited to 4h, 5h or 6h.
[0065] In some optional embodiments, the first aging treatment and the second aging treatment are performed under a protective atmosphere.
[0066] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0067] It should be noted that in the following embodiments and comparative examples, primary rolling refers to the first cold rolling, intermediate rolling refers to the second cold rolling, and finish rolling refers to the third cold rolling; 20% Cu-Ni intermediate alloy refers to a Cu-Ni intermediate alloy in which Ni accounts for 20% by mass, and the same applies to other copper alloys.
[0068] Example 1
[0069] The alloy composition of the present invention is calculated by weight percentage as follows: Co: 1.55%, Ni: 0.55%, Si: 0.43%, Fe: 0.01%, Zn: 0.015%, Mg: 0.01%, Nb: 0.05%, and the balance is Cu. The raw materials are electrolytic copper, 20% Cu-Ni master alloy, 20% Cu-Si master alloy, Co metal, iron wire, zinc ingot, 10% Cu-Mg master alloy and Nb metal. The diameter of the iron wire is 0.5 mm.
[0070] Melting and casting: weigh the raw materials according to the alloy composition ratio, mix them and then melt them in sequence, the melting temperature is 1250℃, stir the raw materials for 5 minutes after melting, the casting temperature is 1210℃, the initial casting speed is 60mm / min, the normal casting speed is 80mm / min, and the initial cooling water flow is 50m 3 / h, normal cooling water flow rate 80m 3 / h, processed into ingots with a width of 630mm and a thickness of 190mm;
[0071] Hot rolling and solution treatment: the ingot is heated by a stepping furnace, the temperature range is 900℃, the rate is 10℃ / min, hot working deformation is carried out at a temperature of 820℃, the plate thickness is 9.5mm, the final rolling temperature is 600℃, and then a solution treatment is carried out, the solution treatment temperature is 650℃, the holding time is 0.5h, and the coiling is carried out after the completion of the first solution treatment. The coiling speed of the hot rolling mill is controlled at 100m / min;
[0072] Milling: Use the milling cutter speed of 850rpm and the machine speed of 6m / min to perform one milling;
[0073] Initial rolling: cold rolling the alloy sheet after milling, the sheet thickness is 0.95mm;
[0074] Secondary solid solution: vertical online continuous annealing method, temperature 820℃, speed 15m / min, fan speed 900rpm, rapid cooling;
[0075] Intermediate rolling: The alloy strip after secondary solid solution is intermediate rolled, and the thickness of the plate is 0.24mm;
[0076] Primary aging: temperature 450℃, holding time 8h, annealing in a mixed atmosphere of hydrogen and nitrogen;
[0077] Finish rolling: The alloy strip after primary aging is finished rolled, and the plate thickness is 0.15mm;
[0078] Secondary aging: The alloy strip after fine rolling is placed in a bell-type annealing furnace for annealing at a temperature of 350°C for 6 hours in a mixed atmosphere of hydrogen and nitrogen;
[0079] Post-processing of polished materials, stretching and straightening.
[0080] Embodiment 2:
[0081] The alloy composition of the present invention is calculated by weight percentage as follows: Co: 1.66%, Ni: 0.45%, Si: 0.53%, Fe: 0.05%, Zn: 0.05%, Mg: 0.04%, Nb: 0.2%, and the balance is Cu. The raw materials are electrolytic copper, 20% Cu-Ni master alloy, 20% Cu-Si master alloy, Co metal, iron wire, zinc ingot, 10% Cu-Mg master alloy and Nb metal. The diameter of the iron wire is 2 mm.
[0082] Melting and casting: weigh the raw materials according to the alloy composition ratio, mix them and then melt them in sequence, the melting temperature is 1270℃, the casting temperature is 1230℃, the initial casting speed is 65mm / min, the normal casting speed is 85mm / min, and the initial cooling water flow is 60m 3 / h, normal cooling water flow rate 100m 3 / h, processed into ingots with a width of 630mm and a thickness of 190mm;
[0083] Hot rolling and solution treatment: the ingot is heated in a stepping furnace at a temperature of 1200°C and a rate of 12°C / min. Hot working deformation is performed at a temperature of 910°C. The plate thickness is 19mm. The final rolling temperature is 685°C. Then a solution treatment is performed at a temperature of 750°C and a holding time of 2h. After the first solution treatment, the ingot is coiled. The coiling speed of the hot rolling mill is controlled at 65m / min.
[0084] Milling: Use the milling cutter speed of 650rpm and the machine speed of 3m / min to perform milling three times;
[0085] Initial rolling: The alloy sheet after milling is cold rolled, and the sheet thickness is 1.9mm;
[0086] Secondary solid solution: vertical online continuous annealing method, temperature 1040℃, speed 25m / min, fan speed 910rpm, rapid cooling;
[0087] Intermediate rolling: The alloy strip after secondary solid solution is intermediate rolled, and the thickness of the plate is 0.48mm;
[0088] Primary aging: temperature 500℃, holding time 5h, annealing in a mixed atmosphere of hydrogen and nitrogen;
[0089] Finish rolling: The alloy strip after primary aging is finished rolled, and the plate thickness is 0.2mm;
[0090] Secondary aging: The alloy strip after fine rolling is placed in a bell-type annealing furnace for annealing at a temperature of 450°C for 4 hours in a mixed atmosphere of hydrogen and nitrogen;
[0091] Post-processing of polished materials, stretching and straightening.
[0092] Embodiment 3:
[0093] The alloy composition of the present invention is calculated by weight percentage as follows: Co: 1.58%, Ni: 0.5%, Si: 0.51%, Fe: 0.02%, Zn: 0.03%, Mg: 0.02%, Nb: 0.03%, and the balance is Cu. The raw materials are electrolytic copper, 20% Cu-Ni master alloy, 20% Cu-Si master alloy, Co metal, iron wire, zinc ingot, 10% Cu-Mg master alloy and Nb metal. The diameter of the iron wire is 2 mm.
[0094] Melting and casting: weigh the raw materials according to the alloy composition ratio, mix them and then melt them in sequence, the melting temperature is 1260℃, the casting temperature is 1220℃, the initial casting speed is 55mm / min, the normal casting speed is 75mm / min, and the initial cooling water flow is 55m 3 / h, normal cooling water flow rate 90m 3 / h, processed into ingots with a width of 630mm and a thickness of 190mm;
[0095] Hot rolling and solution treatment: the ingot is heated in a stepping furnace at a temperature of 1000°C and a rate of 11°C / min. Hot working deformation is performed at a temperature of 900°C. The plate thickness is 12.16mm. The final rolling temperature is 630°C. Then a solution treatment is performed at a temperature of 700°C and a holding time of 1h. After the first solution treatment, the ingot is coiled. The coiling speed of the hot rolling mill is controlled at 80m / min.
[0096] Milling: Use the milling cutter speed of 700rpm and the machine speed of 5m / min to perform milling twice;
[0097] Initial rolling: The alloy sheet after milling is cold rolled, and the sheet thickness is 1.82mm;
[0098] Secondary solid solution: vertical online continuous annealing method, temperature 950℃, speed 20m / min, fan speed 910rpm, rapid cooling;
[0099] Intermediate rolling: The alloy strip after secondary solid solution is intermediate rolled, and the thickness of the plate is 0.46mm;
[0100] Primary aging: temperature 480℃, holding time 6h, annealing in a mixed atmosphere of hydrogen and nitrogen;
[0101] Finish rolling: The alloy strip after primary aging is finished rolled, and the plate thickness is 0.25mm;
[0102] Secondary aging: The alloy strip after fine rolling is placed in a bell-type annealing furnace for annealing at a temperature of 380°C for 5 hours in a mixed atmosphere of hydrogen and nitrogen;
[0103] Post-processing of polished materials, stretching and straightening.
[0104] Comparative Example 1:
[0105] The difference from Example 1 is that the Co element is replaced by the Ni element, and the corresponding alloy raw material is a 20% Cu-Ni master alloy.
[0106] Comparative Example 2:
[0107] The difference from Example 1 is that the content of the Co element and the content of the Ni element in the alloy are exchanged.
[0108] Comparative Example 3:
[0109] The difference from Example 1 is that no Fe and Mg elements are added.
[0110] Comparative Example 4:
[0111] The difference from Example 1 is that no Zn element is added.
[0112] Comparative Example 5:
[0113] The difference from Example 1 is that no Nb element is added.
[0114] Comparative Example 6:
[0115] The difference from Example 1 is that the secondary solution temperature is 800°C.
[0116] Comparative Example 7:
[0117] The difference from Example 1 is that the secondary solid solution speed is 10 m / min.
[0118] Test Example 1
[0119] The properties of the foil materials provided in the above embodiments and comparative examples were tested, and the results are shown in Table 1.
[0120] Table 1
[0121] .
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy foil, characterized in that: Calculated by mass percentage, it includes: Co1.55%~1.66%, Ni 0.45%~0.55%, Si 0.43%~0.53%, Fe 0.01%~0.05%, Zn 0.015%~0.05%, Mg0.01%~0.04%, Nb 0.05%~0.2%, and the balance is copper and unavoidable impurities; In the high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil, the copper matrix grain size is 5-10 μm, and the (Ni, Co)2Si precipitated phase size is ≤15 nm; The method for preparing the high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil comprises the following steps: The ingredients are prepared according to the mass percentage, and then smelting, casting, hot rolling, first solution treatment, milling, first cold rolling, second solution treatment, second cold rolling, first aging treatment, third cold rolling and second aging treatment are carried out in sequence to prepare a high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil; The temperature of the first solution treatment is 650-750°C, and the holding time is 0.5-2h; The second solution treatment is to continuously anneal the alloy material after the first cold rolling; the temperature of the continuous annealing is 820-1040° C. and the speed is 15-25 m / min.
2. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1 is characterized in that: The smelting temperature is 1250-1270°C; The casting temperature is 1210-1230°C.
3. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1, characterized in that: The hot rolling start temperature is 820-910°C; The final rolling temperature of the hot rolling is 600-685°C; The total processing rate of the hot rolling is 90% to 95%.
4. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1, characterized in that: The processing rate of the first cold rolling is 85% to 90%; The processing rate of the second cold rolling is 70% to 80%; The processing rate of the third cold rolling is 20% to 55%.
5. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1, characterized in that: The temperature of the first aging treatment is 450-500° C., and the insulation time is 5-8 hours.
6. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1, characterized in that: The second aging treatment is to anneal the alloy material after the third cold rolling in a bell-type annealing furnace, the annealing temperature is 350-450° C., and the holding time is 4-6 hours.
7. The high-conductivity and high-heat dissipation copper-cobalt-nickel-silicon alloy strip foil according to claim 1, characterized in that: The first aging treatment and the second aging treatment are carried out under a protective atmosphere.
Citation Information
Patent Citations
High-strength Cu-Ni-Co-Si base copper alloy sheet, process for producing same, and current-carrying component
CN104968815A